The Lasker~Koshland Special Achievement Award in Medical Science awarded to Lucy Shapiro - Leslie B. Vosshall (Proceedings of the National Academy of Sciences, 2025)
Scientists can contribute to society in numerous ways. Some scientists discover new biological principles and found entirely new fields. Some scientists are inspiring mentors and create the next generation of inclusive lab leaders. Some scientists are entrepreneurs who develop clinically effective therapeutics. Some scientists are trusted advisors to government and pharmaceutical companies. Some scientists are visionary institutional leaders who build new departments. From this menu of activities, most scientists select two or at most three. It is exceedingly rare for a single scientist to excel in all of these areas, consistently, over the course of a career. Lucy Shapiro is this extraordinary scientist. She founded the field of bacterial cell biology and trained the next generation of microbiologists, launched biotech companies to develop new antifungal drugs, served as an unofficial advisor to two presidential administrations and numerous companies, institutions, and foundations, and built and led successful academic departments. The 2025 Lasker~Koshland Special Achievement Award in Medical Science is awarded to Lucy Shapiro “for a 55-y career in biomedical science—honored for discovering how bacteria coordinate their genetic logic in time and space to generate distinct daughter cells; for founding Stanford’s distinguished Department of Developmental Biology; and for exemplary leadership at the national level.”